The effects of miglitol on the pharmacokinetics of phenytoin in healthy volunteers - Richardt, Denise (My University, 1996)
The interaction between miglitol, an a-glucosidase inhibitor used as an adjunct therapy in diabetes, and phenytoin, an anticonvulsant primarily used in the treatment of epilepsy, was studied over 26 days. Twenty-four healthy male volunteers took part in a placebo controlled, double blind, cross-over study in two phases, to determine the effects of multiple 100mg doses of miglitol on a single 400mg dose of phenytoin sodium. Miglitol or placebo was administered three times daily from Day 1 to Day 5. Phenytoin was administered as a single dose on Day 3 of each phase, after which blood samples were taken at regular intervals. A washout period of 14 days separated the two phases.
Dissertation submitted to the Faculty of Health Sciences, University of the Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science In Medicine
Keywords: Pharmacokinetics; Phenytoin; Diabetes